Gender equality in the Qur’an: An Analysis of surah an-Nisa’ verses 1 and 34 in the exegesis of al-Tabari and al-Rāzī - Ismail, Nurjannah; Firdaus, Muhammad; Darmawijaya, Edi (Universitas Islam Negeri Ar-Raniry, 2024)
Surah An-Nisa' verses 1 and 34 have been central to discussions on gender. According to the interpretations of Imam al-Ṭabarī and Imam al-Rāzī, these verses place women in a subordinate role, both in domestic and non-domestic spheres. This interpretation is considered biased, not reflecting the true essence of the Qur'an. Therefore, further research is necessary to uncover the Qur'an’s intended view on gender in these verses. The study uses a descriptive-analytical method with a qualitative approach, gathering data from books, theses, and articles. The findings reveal that al-Ṭabarī and al-Rāzī's interpretations reinforce male superiority in patriarchal tradition, stating that Eve was created from Adam's rib and that the husband is the absolute leader of the wife. However, contemporary scholars argue that interpreting